Features of sexual nervousness of men and women - Kocherhina, Iryna; Hupalovska, Viktoriya (Journal of Education Culture and Society, 2020)
Aim. The aim is to present the results of research on the sexual nervousness of men and women.Methods. 87 Ukrainian men and women were interviewed. For the analysis of the obtained results, methods of statistical processing of data were used.Results. It has been established that there are differences between men and women in terms of sexual nervousness, attitudes towards pornographic materials, sexual arousal, friendly and exchange approaches to sex, signs of positive relationships with others and self-acceptance. Men are more focused on careful approach to sex and woman on friendly approach. Men are more loyal to pornographic products and reach sexual arousal faster. They have higher levels of sexual nervousness. For both men and women, sexual satisfaction is related to a reduction in sexual nervousness and an increase in a sense of feasibility in a sexual way. Dissatisfaction with a men’s sex life is related to emotional discomfort. With the growth of sexual-neurotic feeling and sexual actions the desire for a technically perfect sexual act increases neglecting other aspects of relationships and partner’s wishes. Women who are dependent on others tend to reject themselves and dissatisfaction with their sexual lives increases.Conclusions. Male and female sexuality is associated with many factors of the individual’s mental life. The experience of subjective well-being and quality of life includes sexual satisfaction.Sexual nervousness is closely related to personal nervousness, which in turn is a set of negative emotional feeling, expressed destructive and inconsistent personality traits, and impedes efficient social and psychological functioning. Sexual nervousness is defined as dissatisfaction, disappointment in sex life that leads to neurotic sexual response – difficulties in controlling the sexual urge, confusion, anxiety, etc.